2014
DOI: 10.1093/nar/gku907
|View full text |Cite
|
Sign up to set email alerts
|

Homodimerization of HYL1 ensures the correct selection of cleavage sites in primary miRNA

Abstract: MicroRNA (miRNA) plays an important role in the control of gene expression. HYPONASTIC LEAVES1 (HYL1) is a double-stranded RNA-binding protein that forms a complex with DICER-LIKE1 (DCL1) and SERRATE (SE) to process primary miRNA (pri-miRNA) into mature miRNA. Although HYL1 has been shown to partner with DCL1 to enhance miRNA accuracy, the mechanism by which HYL1 selects the DCL1-targeted cleavage sites in pri-miRNA has remained unknown. By mutagenesis of HYL1 and analysis of in vivo pri-miRNA processing, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 54 publications
4
51
0
5
Order By: Relevance
“…HYL1 interacts with DCL1 to facilitate efficient and precise miRNA precursor processing (Kurihara et al ., 2006; Dong et al ., 2008; Manavella et al ., 2012a; Yang et al ., 2014). Homodimerization of HYL1 is essential for its functions in miRNA precursor processing (Yang et al ., 2010,2014).…”
Section: Microrna Biogenesis In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…HYL1 interacts with DCL1 to facilitate efficient and precise miRNA precursor processing (Kurihara et al ., 2006; Dong et al ., 2008; Manavella et al ., 2012a; Yang et al ., 2014). Homodimerization of HYL1 is essential for its functions in miRNA precursor processing (Yang et al ., 2010,2014).…”
Section: Microrna Biogenesis In Plantsmentioning
confidence: 99%
“…HYL1 interacts with DCL1 to facilitate efficient and precise miRNA precursor processing (Kurihara et al ., 2006; Dong et al ., 2008; Manavella et al ., 2012a; Yang et al ., 2014). Homodimerization of HYL1 is essential for its functions in miRNA precursor processing (Yang et al ., 2010,2014). HYL1 also affects the splicing of some pri-miRNAs and strand selection from miRNA/miRNA* duplexes in AGO1 loading (Szarzynska et al ., 2009; Manavella et al ., 2012a; Ben Chaabane et al ., 2013).…”
Section: Microrna Biogenesis In Plantsmentioning
confidence: 99%
“…Both HYL1 and SE participate in the different biogenesis modes of plant miRNAs, as mutations in their genes result in a global decrease of miRNA levels (4,5,8,9). These proteins have been implicated in several processes including processing precision (12,14,16,47,48), strand selection (49) and splicing (10,50). In vitro processing studies using MIR167b and MIR166g precursors have shown that DCL1 generates more incorrect cuts in the absence of HYL1, especially near the end of the transcript (12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Resulting MIRNA primary transcripts are then recognized by a dicing complex, that harbors DICER-LIKE1 (DCL1) and the core components HYPONASTIC LEAVES 1 (HYL1), a dsRNA binding protein (4)(5)(6)(7) and the zinc finger domain SERRATE (SE) (8)(9)(10)(11). DCL1, HYL1 and SE interact in vivo and are required for an efficient and precise processing of miRNA precursors (12)(13)(14)(15)(16)(17). Several other factors have been shown to aid on miRNA biogenesis modulating the final levels of the small RNAs [reviewed in (1)].…”
Section: Introductionmentioning
confidence: 99%
“…HYL1 contains two dsRNA binding domain at N-terminal followed by nuclear localization signal and these domains are sufficient for its function (Wu et al, 2007). HYL1 dimerizes through its RNA binding domains and this dimerization is essential for its function (Yang et al, 2014(Yang et al, , 2010. HYL1 binds to the stem region and selects the proper cleavage site on pri-miRNA.…”
Section: Formation and Processing Of Pre-mirnasmentioning
confidence: 99%